Fabrication of Pt-doped carbon aerogels for hydrogen storage by radiation method. (11th October 2018) - Zhong, Minglong; Fu, Zhibing; Mi, Rui; Liu, Xichuan; Li, Xiaojia; Yuan, Lei; Huang, Wei; Yang, Xi; Tang, Yongjian; Wang, Chaoyang
Abstract: A radiation method was investigated to fabricate Pt-doped carbon aerogels (CAsPt). The physicochemical properties of the pristine CAs and CAsPt were systematically characterized by X-ray diffraction, scanning electron microscope, transmission electron microscopy, and nitrogen adsorption measurements. The results showed that not only a great number of Pt nanospheres but also many Pt nanoparticles presented in the network of CAs after radiation. The influence of Pt doping on the hydrogen uptake capacity of CAs was studied. In comparison with the pristine CAs, it was remarkable that the hydrogen uptake capacity of the CAsPt had been significantly enhanced, which was contributed by the hydrogen spillover of Pt. Graphical abstract: We report the first study on the fabrication of Pt-doped carbon aerogels for hydrogen storage by radiation method. Highlights: The Pt-doped carbon aerogels are fabricated by radiation method. Both Pt nanospheres and nanoparticles presented in the framework of carbon aerogels after radiation. The Pt-doped carbon aerogels exhibit enhanced H2 uptake in respect to the pristine carbon aerogels. The spillover effect of Pt has been confirmed by the study.